Post-operative Maternal Complications. A Comparison Between Elective And Emergency Caesarean Sections (Journal of Fatima Jinnah Medical University, 2018)
Introduction: According to available statistics, 29% of hospital deliveries are conducted through LSCS (lower segment caesarean section); 80% of which are emergency caesareans. The indications, complications and feto-maternal outcomes of emergency caesareans differ from elective caesareans.Objective: Comparison of postoperative maternal complications in elective versus emergency caesarean sections.Study Design: Comparative study.Setting: Department of Obstetrics and Gynecology, Unit-I, Sir Ganga Ram Hospital, Lahore.Duration of Study: From January to July 2008.Subjects and Methods: Sixty cases of elective and sixty cases of emergency caesarean sections were included in this study. The cases where elective procedure was used were labeled as Group-A, and those where emergency procedure was carried out were labeled as Group-B.Results: The study used samples comparable on important parameters like age and parity. It was found that although complications occurred in elective as well as emergency caesareans, the ratio of complications was higher in the latter category. Difference of complications was found to be significant for anaemia and postoperative fever only. Apart from identifying the underlying factors that may be responsible for the complications, the study also highlight the importance of proper patient management in preventing the complications from developing in the first place.Conclusion: In emergency caesarean section, maternal morbidity is high. Women undergoing emergency procedures are at high risk, and measures should be taken beforehand to make this procedure as safe as possible.
Keywords: Emergency LSCS, Elective LSCS, Maternal complications